“A House for the Dead” or a Cremation Pyre? The Interpretation of Grave No. 10 Discovered in the Globular Amphora Culture Cemetery in Sadowie in the Sandomierz Upland - Pasterkiewicz, Wojciech (Analecta Archaeologica Ressoviensia, 2024)
The subject of this study is grave no. 10 of the Globular Amphora Culture discovered in cemetery no. 23 in Sadowie near Opatów, in the Sandomierz Upland. Based on observations made during fieldwork as well as analyses of documentation, it was determined that the feature had two stages of use. The first was as an above-ground structure like a house for the dead, in which human corpses were placed for skeletonization. The second one concerned rites during which a cremation pyre was erected and human remains and grave goods were cremated. So far, there are only a few analogies for the aforementioned feature from close-range cultural circles which developed in a similar time horizon (including the Havelian culture, the circle of the Corded Ware Culture).